2021
DOI: 10.1038/s41467-021-26307-7
|View full text |Cite
|
Sign up to set email alerts
|

Boride-derived oxygen-evolution catalysts

Abstract: Metal borides/borates have been considered promising as oxygen evolution reaction catalysts; however, to date, there is a dearth of evidence of long-term stability at practical current densities. Here we report a phase composition modulation approach to fabricate effective borides/borates-based catalysts. We find that metal borides in-situ formed metal borates are responsible for their high activity. This knowledge prompts us to synthesize NiFe-Boride, and to use it as a templating precursor to form an active … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
69
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 85 publications
(73 citation statements)
references
References 59 publications
3
69
1
Order By: Relevance
“…Previous density functional theory calculations suggests that Fe enhances the number of active sites and also stabilizes these active sites . Along with this, the introduction of boron allows for the formation of new active phases, such as the Co or Fe phase, in the pristine framework, which increases the electrocatalytic activity toward OER. , …”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…Previous density functional theory calculations suggests that Fe enhances the number of active sites and also stabilizes these active sites . Along with this, the introduction of boron allows for the formation of new active phases, such as the Co or Fe phase, in the pristine framework, which increases the electrocatalytic activity toward OER. , …”
Section: Resultsmentioning
confidence: 98%
“…58 Along with this, the introduction of boron allows for the formation of new active phases, such as the Co or Fe phase, in the pristine framework, which increases the electrocatalytic activity toward OER. 59,60 4. CONCLUSIONS In this study, we reported the simple and scalable fabrication of amorphous, 1D, Co−Fe−B nanochains using sodium borohydride as a reducing agent.…”
Section: Resultsmentioning
confidence: 99%
“…5 For OER, different metal borides have been evaluated but these studies are limited to alkaline conditions. 6,[19][20][21][22]31 Alkaline OER currently has lower technological importance as all current industrial membrane-based electrolyzers operate in acidic media due to restrictions on ionconductive membranes. 17 IrO 2 is state-of-the-art acidic OER catalysts, but is not sustainable due to the scarcity of Ir.…”
Section: Resultsmentioning
confidence: 99%
“…20 However, metal borides show good OER stability in general and treating Ni 3 B powders with concentrated hydrochloric acid results in no detectable changes, making such borides good candidates for use in acidic conditions. 21,22 In this work, we investigated the use of Ni suggest that the addition of Ni 3 B as a supporting material can be beneficial to reduce use of…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, the large-scale commercialization of noble metals for water electrolysis is severely hindered by their scarcities and instability in electrolytes at high potentials. Given this, transition metal (TM)-based oxides, carbides, nitrides, sulfides, phosphides, chalcogenides, hydroxides, halides, alkoxides, and borides/borates have been explored [24][25][26][27][28][29][30][31][32][33][34][35][36][37][38]. Unfortunately, most of these materials exhibit a low catalytic performance, impecunious electronic conductivity, passivation, and dissolution under strongly acidic conditions, hindering their practical application [21,22,39].…”
mentioning
confidence: 99%